Rancang Bangun Sistem Monitoring Ruang Hidroponik Berbasis Mikrokontroler Nodemcu Dengan Penjadwalan Pemberian Nutrisi Otomatis - Anggoro, Dimas Bayu; Armanto, Armanto; Hidayat, Asep Toyib; Karman, Joni (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Indonesia has vast agricultural and plantation lands, yet the efficiency and productivity of this sector still need improvement. One solution is the application of Internet of Things (IoT) technology in hydroponic systems, allowing for automatic and real-time control and monitoring of plant conditions. This research aims to develop a hydroponic room monitoring system based on the NodeMCU microcontroller with automated nutrient scheduling. The methods used in this study include the design and implementation of an IoT system using NodeMCU, humidity sensors, temperature sensors, and nutrient pumps, as well as the development of a smartphone application for monitoring and control. The research results show that the developed system can accurately monitor hydroponic environmental conditions and automatically provide nutrients according to the scheduled time. The use of this technology is expected to facilitate farmers in monitoring and maintaining hydroponic plants, improving water and nutrient use efficiency, and optimizing crop yields. In conclusion, the application of IoT in hydroponic systems positively impacts agricultural productivity, especially in areas with limited land, and offers a practical solution for urban communities interested in modern agriculture.